2x-6=3x+2-x-7

Simple and best practice solution for 2x-6=3x+2-x-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-6=3x+2-x-7 equation:


Simplifying
2x + -6 = 3x + 2 + -1x + -7

Reorder the terms:
-6 + 2x = 3x + 2 + -1x + -7

Reorder the terms:
-6 + 2x = 2 + -7 + 3x + -1x

Combine like terms: 2 + -7 = -5
-6 + 2x = -5 + 3x + -1x

Combine like terms: 3x + -1x = 2x
-6 + 2x = -5 + 2x

Add '-2x' to each side of the equation.
-6 + 2x + -2x = -5 + 2x + -2x

Combine like terms: 2x + -2x = 0
-6 + 0 = -5 + 2x + -2x
-6 = -5 + 2x + -2x

Combine like terms: 2x + -2x = 0
-6 = -5 + 0
-6 = -5

Solving
-6 = -5

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 3x+5-2x=-4(x+2)-7 | | 75+0.30m=105.60 | | .013x^2-1.18x+28.24=4 | | 4x^3+4x^2y+4xy^2+4y^3=8xy+4x^2 | | A=5000+5000*.0425*9.4 | | 3.5x+(-35)+(-45)=180 | | 7(b+3)-18(1-b)=103 | | 16d-(2-5d)=-67 | | 6x=2k+45 | | 6d+4d-2d-7=5d | | A=5000+5000*.425*9.4 | | X-7=18y | | x^2+30x=90 | | 2x-7=3x+1-x-7 | | f(x)=4x^2+2x+10 | | 1.89+a=7.14 | | 5q+6=q-6 | | 8(2x+1)=40-16x | | 2y-5x=-15 | | -4(z+7)=7-3z | | A=5000+5000*.425*.33 | | 5(5x-3)=4x-6 | | (12A^2B+A-5A^2B+2AB)-(4AB^2+6AB-2A-3AB)= | | v^2+5v+7vq+35q=0 | | 5(5x-3)=4x+6 | | 14+3n=-3(n-4) | | 16+.20x=30 | | -3y+28=ysq | | -2(w-7)+12w=34 | | 23c+20=29c+74 | | 8=17.666c | | 16+.20x=306 |

Equations solver categories